The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.7860/jcdr/2014/7348.3921
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Predictors for Post Laparotomy Abdominal Wound Dehiscence

Abstract: Abdominal wound dehiscence after laparotomy is a surgical emergency with high morbidity and mortality leading to escalation in hospital costs and prolonged illness. This complication can be avoided if the factors involved in wound dehiscence are properly addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 10 publications
1
6
1
2
Order By: Relevance
“…[12] Various study done by Maingot, [13] Wolff10, Garg R et al and Muneiah SN et al who observed that old age (45 years) as an independent risk factor for AWD. [14,15] Almost similar results were obtained in our study. The mean age in our study was 48.02±19.39 years.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…[12] Various study done by Maingot, [13] Wolff10, Garg R et al and Muneiah SN et al who observed that old age (45 years) as an independent risk factor for AWD. [14,15] Almost similar results were obtained in our study. The mean age in our study was 48.02±19.39 years.…”
Section: Discussionsupporting
confidence: 91%
“…The present study showed 31.7% of patient had preoperative serum albumin values more than 3 mg/dl. Garg R et al also reported a higher incidence of burst abdomen in patients having renal failure, [14] 38% of patients were having uraemia. However, Afzal S and Bashir M.M reported little or no contribution of uraemia in wound dehiscence.…”
Section: Discussionmentioning
confidence: 92%
“…Out of these patients, 20 (13%) cases were afflicted with wound dehiscence, and the rate of wound dehiscence was higher in males (P=0.013) as reported in most studies (9-12). There was no significant relationship between the age of patients and wound dehiscence in the present study; nonetheless, a study by Ramneesh et al (2014)indicated that old age, particularly the fourth decade of life, contributed to the development of wound dehiscence. Moreover, in their study, Gabrielle et al (2010) referred to age as one of the risk factors for wound dehiscence.…”
Section: Discussioncontrasting
confidence: 75%
“…The incidence reported in the studies ranges from 0.3%-3.5%; nonetheless, it has been reported as 10% in some other studies (4)(5)(6). The influential factors affecting wound dehiscence are assigned to three categories: preoperative, intraoperative, and postoperative (7)(8)(9)(10). Among these factors, we can refer to chronic obstructive pulmonary disease, male gender, age> 40 years, smoking, Body mass index> 30, anemia, low albumin, high bilirubin, ascites, infection, long operative time, postoperative trauma, inexperienced surgeon, peripheral vascular disorders, and strain (10,(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Incidência das lesões confundidoras da lesão por pressão em unidade de terapia intensiva oncológica suficiente de precursores, cofatores e fonte de energia. A desnutrição afeta negativamente a evolução clínica dos indivíduos por aumentar o tempo internação, a incidência de complicações pós-operatórias, como infecções e retardo na epitelização de feridas, além de aumentar a taxa de mortalidade 15 . Condições clínicas tais como caquexia/ anorexia, desnutrição, anemias, síndromes metabólicas, idade avançada e distúrbios circulatórios comprometem a saúde da pele 16 .…”
Section: Resultsunclassified